Analisis Kesulitan Belajar Siswa dalam Pembelajaran Matematika - Sahabat Halawa; Ratna Natalia Mendrofa; Yulisman Zega; Yakin Niat Telaumbanua (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The factors causing students' learning difficulties are highly varied, including in mathematics education. Learning difficulties refer to the various challenges or barriers individuals face in the learning process, which can impact their ability to acquire, process, and apply knowledge and skills. Due to their diverse nature, these difficulties affect various aspects of the learning process. This study aims to describe the learning difficulties students face, particularly in mathematics education. The sample for this study comprises 25 students, specifically all students in class VIII-B. The data collection methods include tests, interviews, and documentation as supplementary data. The analysis reveals that 48% of the students fall into the "moderate" category of mathematics learning difficulties, while 40% are categorized as experiencing "difficult" challenges in learning mathematics. Specifically, in the topic of exponentiation, these learning difficulties stem from challenges in mastering and understanding the concepts, particularly in solving mathematical problems, and difficulties in number operations or lacking operational skills, leading to incorrect problem-solving. Interview results further support that students continue to experience significant difficulties in learning mathematics, especially in the topic of exponentiation.